Edukasi Berbasis Kearifan Lokal untuk Peningkatan Pengetahuan dan Keterampilan Masyarakat dalam Pengendalian Penyakit Tidak Menular - Yosi Suryarinilsih; Lola Felnanda Amri; Murniati Murniati; Sila Dewi Anggreni; Zurni Nurman (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
Non-Communicable Diseases (NCDs) remain a major global health challenge, contributing significantly to morbidity and mortality. Effective NCD control requires community empowerment through education and mentoring based on local wisdom. This community service program aimed to improve public knowledge, early detection behavior, and skills in NCD prevention and control. The program was conducted from June to July 2025 in Padang Sarai and Batipuh Panjang, Padang City, involving 70 community participants with support from lecturers, students, and primary healthcare workers. A participatory community-based approach was implemented through three stages: health screening, education and training, and evaluation. Educational activities included sessions on hypertension, balanced nutrition, hypertension exercise training, and the use of local plants such as cucumber, bay leaves, and celery as evidence-based herbal therapies, as well as cardiovascular emergency education. Evaluation using pre- and post-tests showed an increase in knowledge scores from 60 % to 88,6%; 90% of participants understood local herbal use, 84,3% could perform hypertension exercises, 92,86 % mastered healthy eating patterns, and 85,7 % recognized heart attack signs. These findings indicate that integrated educational approaches rooted in local wisdom effectively empower communities and enhance NCD prevention capacity.